Data on land snails (Gastropoda) in Tay Trang area, Dien Bien province - Nhuong, Do Van; Dung, Dinh Phuong (Academia Journal of Biology, 2012)
Tay Trang in Dien Bien province is a border area close to the Lao People’s Democratic Republic. So far, there is no data about land snails (Gastropoda) in this region. Our paper reports 54 species of land snails, belonging to 35 genera, 15 families, 3 orders and 2 subclasses, such as Prosobranchia and Pulmonata. Of the total, Pulmonata is accounted for 70.4% and Prosobranchia is 29.4%. According to the number of species the Cyclophoridae is the most abundant family (9 species) and Ariophantidae (8 species), the others are fewer in number. The land snails species found are distributed among the three habitats: forest on limestone mountains, forests on the hills and forests on the granite mountains. The most abundant species were encountered in limestone halutats, accounting for 88.9% of species, the least abundant species encountered in forest on the hill. Average density of individual on limestone reaching to 33 individuals per m2, the lowest density (4 individuals per m2 ) is found an forest hills.